Assessment of mechanical, thermal properties and crystal shapes of monoclinic tricalcium silicate from atomistic simulations - Claverie, Jérôme [UNESP]; Kamali-Bernard, Siham; Cordeiro, João Manuel Marques [UNESP]; Bernard, Fabrice (Elsevier, 2021)
The two most common polymorphs in industrial alite, M1 and M3, were characterized at the molecular scale. Different methods were employed and discussed to assess mechanical properties and specific heat of both polymorphs. The calculated homogenized elastic moduli and specific heat were found in good agreement with experimental measurements. A comparative analysis of spacial Youngs modulus reveal isotropic and anisotropic spacial distribution for M1 and M3 respectively. A more isotropic compressive strength is also reported for M1 when compared to M3 polymorph. Cleavage energies computation allowed to proposed equilibrium shapes for both polymorph, with significant differences. While the lowest cleavage energies were found along (100) and (001) for both polymorphs, the constructed M1 crystal possesses 3 independent facets, against seven for the M3 polymorph.
Keywords: Cleavage energy; Crystal shape; Mechanical properties; Molecular dynamics; Thermal properties; Tricalcium silicate